Faktor-Faktor yang Berhubungan dengan Kesiapan Kader Posyandu ILP di Wilayah Kerja Puskesmas Penusupan Kabupaten Tegal Tahun 2026 - Valentina Ayumy Fortunita Mia Amrillah; Lely Wahyuniar; Dwi Nastiti Iswarawanti; Mamlukah Mamlukah (Jurnal Sains dan Kesehatan, 2026)
The Integrated Primary Care Posyandu (ILP) program requires cadres to assume a much broader role compared to conventional Posyandu services. In the working area of Puskesmas Penusupan, ILP achievement reached only 20% in 2025, while merely 25 out of 225 cadres (11%) had received related training. This condition indicates that cadre readiness needs to be examined more comprehensively before the program can be implemented optimally. This study aimed to analyze the factors associated with the readiness of ILP Posyandu cadres using a descriptive-analytic method with a cross-sectional approach. The study involved 144 cadres selected proportionally from a population of 225 using the Slovin formula. Data were collected through structured interviews using a validated questionnaire and analyzed using univariate, bivariate (Spearman Rank), and multivariate (ordinal logistic regression) analyses. The results showed that among the eight variables examined, only skills (r = 0.171; p = 0.040) and resource availability (r = 0.225; p = 0.007) were significantly associated with cadre readiness. In the multivariate analysis, resource availability emerged as the most influential factor with an OR = 2.839 (95% CI: 1.311–6.149), indicating that cadres supported by adequate resources were 2.8 times more likely to demonstrate good readiness. In conclusion, resource availability was identified as the dominant factor associated with the readiness of ILP Posyandu cadres in the working area of Puskesmas Penusupan. Therefore, improving the availability of facilities and infrastructure, providing practice-based training, and strengthening operational support should become priority programs in the future.